2021
DOI: 10.3389/fgene.2021.687844
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Chloroplast Genome for Four Pennisetum Species: Molecular Structure and Phylogenetic Relationships

Abstract: The genus Pennisetum (Poaceae) is both a forage crop and staple food crop in the tropics. In this study, we obtained chloroplast genome sequences of four species of Pennisetum (P. alopecuroides, P. clandestinum, P. glaucum, and P. polystachion) using Illumina sequencing. These chloroplast genomes have circular structures of 136,346–138,119 bp, including a large single-copy region (LSC, 79,380–81,186 bp), a small single-copy region (SSC, 12,212–12,409 bp), and a pair of inverted repeat regions (IRs, 22,284–22,3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 82 publications
(94 reference statements)
3
5
0
Order By: Relevance
“…The SSRs numbers in the LSC region of plastome of R. coccinea and R. philippinensis are 53 and 47, respectively. The distribution of SSR in the four species of Renanthera was consistent with that of most angiosperms (Xu et al, 2021;Sun et al, 2022;Xia et al, 2022).…”
Section: Discussionsupporting
confidence: 68%
“…The SSRs numbers in the LSC region of plastome of R. coccinea and R. philippinensis are 53 and 47, respectively. The distribution of SSR in the four species of Renanthera was consistent with that of most angiosperms (Xu et al, 2021;Sun et al, 2022;Xia et al, 2022).…”
Section: Discussionsupporting
confidence: 68%
“…The results of this study provide strong evidence for elucidating the evolutionary history of these species and deeply analyzing the evolutionary events of Catalpa and even Bignoniaceae. The further development of sequencing technology will help fully reveal the general characteristics and patterns of variation of the chloroplast genome and provide a foundation for resolving the differences between morphological and genetic classification and for obtaining an in-depth understanding of plant evolution ( Xu et al, 2021 ). However, due to the limited number of published chloroplast genomes of taxa within the genus Catalpa , there are still many difficulties in phylogenetic studies of this group.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, chloroplast markers and complete chloroplast genomes of plants have been widely used and have made significant contributions to phylogeny reconstruction at different taxonomic levels in plants [31,32] including species of the genus Pulsatilla [33][34][35][36]. Plastid phylogenomic analyses, among others, showed that the species of Pulsatilla formed a monophyletic group, and should not be synonymized with the genus Anemone.…”
Section: Discussionmentioning
confidence: 99%